2009 IEEE International Conference on Robotics and Automation 2009
DOI: 10.1109/robot.2009.5152526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compliant ankles on bipedal locomotion

Abstract: The influence of ankle compliance on bipedal robot locomotion is investigated in this paper. The focus is on reduction of energy consumption. The concept of hybrid zero dynamics is adapted to design walking gaits with three phases: underactuated heel roll, full actuation and underactuated toe roll. Ankle springs work in parallel with the ankle actuators. Stiffness and offset of the linear torsional springs at the ankle and gait parameters are optimized simultaneously. It is shown that simultaneous optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
17
2
Order By: Relevance
“…This is contrary to Ref. 7 and Ref. 10 where they found ankle springs useful for stability and energetic efficiency.…”
Section: Resultscontrasting
confidence: 76%
“…This is contrary to Ref. 7 and Ref. 10 where they found ankle springs useful for stability and energetic efficiency.…”
Section: Resultscontrasting
confidence: 76%
“…Figure 3 shows that the optimization criterion is significantly reduced after introducing identical springs to both hip joints in parallel with existing actuator. It was however observed that adding springs to both knees or ankles were not effective in our case contrary to [19], [24] where they found ankle springs useful for stability and energetic efficiency. This is because we considered a flat foot impact and there is no double support phase and no rotation of support foot during entire swing phase.…”
Section: The Optimization Constraintscontrasting
confidence: 83%
“…The number of humanoid robots having arms, head and feet are increasing and researchers are concentrating on the energetic effects of arms, feet and compliance in the walking gaits by adding springs to the bipeds. Most of the researchers including [6], [19], [20], [17] are motivated by the hypothesis that bipeds with compliant ankles may be able to exhibit more natural-looking gaits with better energetic efficiency and walking stability as compared to bipeds without compliant joints. Several researchers studied that the design of the knee joint can help to improve the walking efficiency [10] and others concentrated on the addition of passive elastic members in the knee and hip joints.…”
Section: Introductionmentioning
confidence: 99%
“…In [6] is a domain not seen in the human walking wherein the biped only has one contact point at the right heel (see Fig. 11 for an illustration).…”
Section: Computing the Human-based Costmentioning
confidence: 99%
“…Traditionally, most models of bipedal robots have employed a single domain model [1][2][3][4], which assumes an instantaneous double support phase and usually excludes the presence of feet (models of this form began with the so-called compass gait biped, which did not have knees or feet). Adding feet to the bipedal robot results in the need to extend the domain breakdown beyond a single discrete phase, which is typically done by either adding a phase where the heel is off the ground or a double support phase where both feet are on the ground, or any combination thereof [5][6][7]. This lack of consistency among models in the literature motivates the desire to determine if there does in fact exist a single ''universal'' domain breakdown that should be used when modeling bipedal robots, especially in the context of obtaining human-like bipedal walking.…”
Section: Introductionmentioning
confidence: 99%